Prediktor Prestasi Belajar Matematika Siswa: Peran Motivasi, Kecemasan, dan Self-Efficacy - Wulandari, Andhika Ayu; Kurniawati, Oktavia (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to determine the effect of learning motivation, mathematics anxiety, and self-efficacy on the mathematics achievement of seventh-grade students at SMP Negeri 3 Tegalombo. The data collection technique used was a questionnaire, which was distributed to all seventh-grade students at SMP Negeri 3 Tegalombo as respondents of this study. The sampling technique used was a saturated sample in which the entire population was sampled. Data analysis used descriptive analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination, F-tests, and t-tests. The results of the prerequisite test show that the variables of learning motivation, mathematics anxiety, self-efficacy, and mathematics achievement are normally distributed, and there is no multicollinearity or heteroscedasticity. By testing the hypothesis, it is known that learning motivation, mathematics anxiety, and self-efficacy simultaneously have a positive and significant effect on the mathematics achievement of seventh-grade students at SMP Negeri 3 Tegalombo by 32.9%. Partially, the variables of motivation and self-efficacy influence mathematics learning achievement, but the variable of mathematics anxiety does not affect the mathematics achievement of seventh-grade students at SMP Negeri 3 Tegalombo.